Triply periodic minimal surface lattices additively manufactured by selective laser melting - Yan, Chunze; Hao, Liang; Yang, Lei; Young, Philippe G.; Li, Zhaoqing; Li, Yan (3D Printing Technology Series., 2021)
"[P]resents the design, manufacturing, microstructure, mechanical properties and applications of TPMS structures fabricated by selective laser melting--the most commonly used AM technology for TPMS. The book explains these complex and useful structures, based on systematic work conducted in the United Kingdom and in China"--Print version, page 4 of cover.